Promotion of hMDSC differentiation by combined action of scaffold material and TGF-β superfamily growth factors - Airina Mazetyte-Godiene; Agne Vailionyte; Tadas Jelinskas; Jaroslav Denkovskij; Arvydas Usas (Regenerative Therapy, 2024)
Objective: Herein we propose a combined action of collagen type I (CA) or synthetic collagen-like-peptide functionalized with the cell adhesive RGD motif (PEG-CLP-RGD) hydrogels and selected growth factors to promote chondrogenic differentiation of human muscle-derived stem cells (hMDSCs) under normal and reduced oxygen conditions. Methods: hMDSCs were set for differentiation towards chondrogenic lineage using BMP-7 and TGF-β3. Cells were seeded onto hydrogels loaded with growth factors (75ng/scaffold) and cultured for 28 days under normal (21%) and severe hypoxic (1%) conditions. Chondrogenesis was evaluated by monitoring collagen type II and GAG deposition, and quantification of ACAN expression by RT-PCR. Results: Sustained release of TGFβ3 from the hydrogels was observed, 8.7 ± 0.5% of the initially loaded amount diffused out after 24 h from both substrates. For the BMP-7 growth factor, 14.8 ± 0.3% and 18.2 ± 0.6% of the initially loaded amount diffused out after 24 h from CA and CLP-RGD, respectively. The key findings of this study are: i) the self-supporting hydrogels themselves can stimulate hMDSC chondrogenesis by inducing gene expression of cartilage-specific proteoglycan aggrecan and ECM production; ii) the effect of dual BMP-7 and TGF-β3 loading was more pronounced on CA hydrogel under normal oxygen conditions; iii) dual loading on PEG-CLP-RGD hydrogels did not have the synergistic effect, TGF-β3 was more effective under both oxygen conditions; iv) BMP-7 can improve chondrogenic effect of TGF-β3 on CA scaffolds, and hydrogels loaded with both growth factors can induce cartilage formation in hMDSC cultures. Conclusion: Our results support the potential strategy of combining implantable hydrogels functionalized with differentiation factors toward improving cartilaginous repair.